Review of the management of childhood asthma in Tasmania. Issue 8 (9th June 2013) - Bereznicki, Bonnie J; Norton, Lucy C; Beggs, Sean A; Gee, Peter; Bereznicki, Luke RE
<x xml:space="preserve">Abstract</x> Aim To review the supply of medications to children with asthma and parent‐reported management of childhood asthma in Tasmania and highlight evidence‐practice gaps for future interventions. Methods Participating pharmacies ran a software application that extracted data from dispensing records and helped to identify children with asthma. Parents of identified children were mailed a survey evaluating components of asthma management. Dispensing and survey data were analysed. Results A total of 939 children from 23 pharmacies were identified by the software and deemed eligible for inclusion. Surveys were received from 353 (37.6%) parents. In the past year, short‐acting beta‐2 agonists were supplied to 56.1% of the cohort, preventers to 76.5% (inhaled corticosteroids 52.3%; leukotriene receptor antagonists 31.3%; inhaled cromones 0.6%), long‐acting beta‐2 agonists (LABAs) to 25.7% and oral corticosteroids to 21.5%. Approximately half of the children receiving inhaled corticosteroids were concurrently receiving a LABA. Among children with indicators of inadequately controlled asthma, up to 73.7% of their parents reported that their asthma was adequately controlled, up to 38.2% did not possess an Asthma Action Plan, up to 36.8% were not regularly using a spacer and up to 22.8% had not received a preventer. Conclusion These results indicate gaps in childhood asthma management, in particular, undersupply of preventers in high‐risk patient groups, high supply of LABAs and insufficient spacer and asthma action plan usage. These areas should be targeted for interventions to improve childhood asthma management.